Parental Beliefs and Practices Surrounding the Development of EmergentLiteracy - Carla Muñoz; Nicole Frez-Aróstica (Universidad Autónoma de Baja California, 2021)
This study describes family beliefs and practices surrounding early literacy in households from disadvantaged backgrounds and involved 79 families of children aged between 1.5 and 5 years of age from six educational facilities in two regions in southern Chile. Participants answered a questionnaire that aimed to explore family beliefs and practices relating to emergent literacy. The results show high exposure to television during free time and the use of language to regulate behavior. As far as reading practices are concerned, most of those surveyed reported explicitly and systematically teaching their children letters, but most state that they do not read for pleasure. The results support the idea of working in networks with families and developing parental practices that promote early childhood literacy in the home.